EXTERNAL LABOR MIGRATION OF CITIZENS OF THE KYRGYZ REPUBLIC IN THE CONTEXT OF GLOBAL TRANSFORMATIONS: DYNAMICS, TRENDS AND CHALLENGES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article is devoted to the study of external labor migration of citizens of the Kyrgyz Republic in the context of global socio-economic and geopolitical transformations. The key directions of migration flows, their dynamics and structural changes in recent years are considered. Special attention is paid to the impact of labor migration on the country’s economy, including the volume and structure of remittances, their role in shaping GDP, as well as social and demographic consequences. New trends are analyzed, such as the diversification of destination countries, the growing interest in alternative labor markets, and the development of digital forms of employment. Based on the analysis, the directions of state policy aimed at diversifying labor migration, improving the skills of employees and developing alternative forms of employment are proposed.
Keywords: External labor migration, Kyrgyz Republic, global transformations, migration flows, remittances, digitalization of employment, social consequences, international labor market.